Autoantibodies in sera of patients with hepatocellular carcinoma - KAMEKO, Mitsuaki; KANAI, Masamitsu; KUMAGAI, Toshiko; FURUTA, Seiichi; KIYOSAWA, Kendo; IMAI, Haruhiko (Kanzo, 1986)
Autoantibodies including antinuclear antibody, antismooth-muscle antibody, antimitochondrial antibody, rheumatoid factor, lupus erythematosus factor, antimicrosomal antibody and antithyroglobulin antibody were assayed in 70 sera of hepatocellular carcinoma, 31 sera of liver cirrhosis, 32 sera of chronic hepatitis, 60 sera of non-hepatic tumors and 145 normal subjects. A significantly high prevalence of antinuclear antibody was found in patients with hepatocellular carcinoma (24.3%) and with non-hepatic tumors (23.3%). Antinuclear antibody in sera of hepatoma patients was not correlated with other autoantibodies and also with hepatitis B surface antigen, sex and age. Serial assays of antinuclear antibody in sera of different stages from precancerous stage to cancerous stage and/or after resection of hepatic tumor were done in 10 patients with hepatocellular carcinoma whose sera were positive for antinuclear antibody. Antinuclear antibody became positive with the evolution of hepatoma in 2 patients, and disappearance of antinuclear antibody was observed in one patient after resection of hepatic tumor. The contribute significance of antinuclear antibody in serum of hepatoma is not clear, but in some patients with hepatocellular carcinoma, antinuclear antibody can behave like tumor-marker.